New copolyesters derived from terephthalic and 2,5-furandicarboxylic acids: A step forward in the development of biobased polyesters - Sousa, Andreia F.
A straightforward partial substitution of non-renewable poly(ethylene terephthalate) by renewable homologous poly(ethylene furandicarboxylate) was successfully done by random copolymerisation of bis(2-hydroxyethyl) terephthalate and bis(hydroxyethyl)-2,5-furandicarboxylate. Different stoichiometric amounts of these monomers were used and the ensuing copolyesters were characterised in detail by several physical chemistry, thermal and mechanical techniques. All copolyesters have the expected chemical structure incorporating both aromatic and furanic units in different amounts accordingly to the stoichiometric feed-ratio. In particular the copolyester having 20% of furan units (PET-ran-PEF 4/1) have similar properties to those of PET homopolyester, despite some minor differences, being a semi-crystalline copolyester with similar glass transition and melting temperatures to those of PET. Also, the mechanical performance of this PET-ran-PEF 4/1 copolyester was in accordance with the PET operating temperature range, tan delta and modulus. (C) 2012 Elsevier Ltd. All rights reserved.